Addressing current challenges in adult nursing: Describing a virtual Consensus development project methodology - Bethany Taylor; Jane South; Steve Robertson; Tony Ryan; Emily Wood; Rachel Louise King; Michaela Senek; Angela Tod; Jane Seymour (Wiley, 2022)
Abstract Aim This article describes the development and implementation of a virtual Consensus development project to address current challenges in adult nursing care in the UK. Design This is a Consensus Development Project (CDP). Methods The five stages of this CDP were: develop questions (informed by PPI representatives and a documentary review), generate evidence reviews, recruit and orient the lay panel, host Consensus seminars, and consult with panel members and stakeholders. Results To the best of our knowledge, a CDP has not previously been conducted in a UK nursing context, and this is the first of its kind to be hosted virtually. This article contributes a detailed outline of the Consensus development methodology and constructive commentary to support future Consensus development projects. Learning points include reflections on the impact of hosting this event virtually, the relationship between the project coordinator and chair, and the composition of the lay panel.